Challenges in Implementing Learner-Centered Method for English Language Teaching in Tanzanian Secondary Schools - Siriel Mhando; Mustapha Almasi (FOSTER: Journal of English Language Teaching, 2024)
Learner-centred methods (LCM) are vital in improving students’ cognitive, however, they are lowly practised by teachers in Tanzania. This study explores LCM used by teachers in teaching English Language, challenges related to the use of LCM and how teachers respond to the challenges in the selected schools. Fifty (50) teachers from secondary school deemed to use LCM were selected. A descriptive study design was used. Data were collected through interviews and then analysed through content analysis. The findings reveal that teachers in visited schools preferred using debate, group discussions and probing questions and answers. Nonetheless, shortage of study materials, time factor, large number of students in classes and students being uncomfortable with the methods were reported as key challenges. Teachers responded to the challenges by setting separate learning sessions, borrowing learning materials from other schools and setting extra hours. The findings of this study informs the need for interventions to promote the effective implementation of learner-centered methods. This study adds to the empirical evidence regarding the use of LCMs in English Language teaching especially in poor resource countries.